A High-Tryptophan Diet Reduces Seizure-Induced Respiratory Arrest and Alters the Gut Microbiota in DBA/1 Mice - Yue, Qiang; Cai, Mingfei; Xiao, Bo; Zhan, Qiong; Zeng, Chang (Frontiers in Neurology, 2021)
Background and Aims: Central 5-hydroxytryptamine (5-HT) defects are responsible for the occurrence of sudden unexpected death in epilepsy (SUDEP). The DBA/1 mouse is an animal model of SUDEP since the mouse exhibits audiogenic seizure-induced respiratory arrest (S-IRA). The synthesis of central 5-HT is closely related to the gut microbiota. Moreover, emerging studies suggest a possible role for the microbiota in mitigating seizure likelihood. Based on this, we aimed to explore the effect of a high-tryptophan diet (HTD) on SUDEP as well as the synthesis and metabolism of central 5-HT. Furthermore, we investigated the involvement of the gut microbiota in this process. Methods: All DBA/1 mice were subjected to acoustic stimulation to induce seizures. Only mice that exhibited S-IRA were randomly assigned to the normal diet (ND) group (n=39) or HTD group (n=53). After one month of dietary intervention, 1) S-IRA rates were evaluated, 2) the concentrations of 5-HT and its metabolite 5-hydroxyindoleacetic acid (5-HIAA) in the plasma and brain were determined by ultra-high-pressure liquid chromatography, and 3) the faecal flora biodiversity and species composition were analysed by 16S rDNA microbiota profiling. Results: The S-IRA rate in DBA/1 mice was significantly reduced in the HTD group compared with that in the control group. HTD increased the levels of 5-HT and 5-HIAA in both the telencephalon and midbrain. HTD significantly elevated the species richness and diversity of the gut microbiota. Moreover, there was a significant difference in the gut microbiota composition between the two groups, and the intestinal flora was dominated by Proteobacteria and Actinobacteria after HTD. Conclusions: HTD is efficient in lowering S-IRA rates and elevating the central 5-HT level in DBA/1 mice. The gut microbiota was altered after HTD intervention. The significant increase in Proteobacteria and Actinobacteria may be related to the SUDEP-protective effect of HTD. Our findings shed light on a candidate choice of dietary prevention for SUDEP.